2019
DOI: 10.1136/bmjopen-2018-025417
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal herb use andChlamydia trachomatisinfection: cross-sectional study among women of various ethnic groups in Suriname

Abstract: ObjectiveVaginal steam baths with herb leaves (herb use) is practised by some Surinamese women. We assessed herb use among women from the five most prevalent ethnic groups, and if herb use is associated withChlamydia trachomatisinfection.SettingParticipants were recruited at a sexually transmitted infection (STI) clinic and a family planning clinic (FP) in Paramaribo, Suriname.Participants1040 women were included subsequently, comprising the following ethnic groups: Creole (26.7%), Hindustani (24.6%), Javanese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In the current "Internet+" era, the online maker education form for undergraduates is gradually popularized and promoted. Meanwhile, the seamless development of offline and online education can promote the comprehensive development of maker education (Van der Helm et al, 2019). Based on the thinking of "Internet + Maker Education" and the current situation of maker education in universities, this study proposed the construction structure of maker education on the Internet platform based on the function of learning space, as shown in Figure 1.…”
Section: Ie Education Model Based On "Internet + Maker Education"mentioning
confidence: 99%
See 1 more Smart Citation
“…In the current "Internet+" era, the online maker education form for undergraduates is gradually popularized and promoted. Meanwhile, the seamless development of offline and online education can promote the comprehensive development of maker education (Van der Helm et al, 2019). Based on the thinking of "Internet + Maker Education" and the current situation of maker education in universities, this study proposed the construction structure of maker education on the Internet platform based on the function of learning space, as shown in Figure 1.…”
Section: Ie Education Model Based On "Internet + Maker Education"mentioning
confidence: 99%
“…Therefore, the target positioning of undergraduates mainly depends on the general process of maker activities. Universities are the major environments for cultivating maker talents (Van der Helm et al, 2019). In such an environment, teaching and scientific research work are completed.…”
Section: Ie Education Model Based On "Internet + Maker Education"mentioning
confidence: 99%
“…Hence, 96.6% of maroon women perform steam baths while only 4.2% of Amerindian women do ( 47 ); The hypothesis is that such practices lead to a dry vagina, with a modification of the protective bacterial flora and increased risks for microlesions and subsequent infections. A study in Suriname suggested that regarding Chlamydia infection steam baths were not particularly associated with more Chlamydia ( 52 ). Hypothesizing that, if steam baths made women more vulnerable to sexually transmitted infections (they are usually first practiced after the first menses), there should be a differential incidence for HIV and HTLV-1, we surveyed historical data on both HIV and HTLV-1( 53 ) and there was no such difference which is not in favor of a large effect of vaginal steam baths as a major epidemic driver.…”
Section: Potential Drivers Of Stis In the Maroni Areamentioning
confidence: 99%